Penerapan Model Pembelajaran SETS (Science, Environment, Tecnology and Society) untuk Meningkatkan Hasil Belajar PLH - Aufa, Ismi Nabila; Ismail, Ali; Syahid, Aah Ahmad (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research aims to improve student learning outcomes in Environmental Education (PLH) subjects through the application of the SETS (Science, Environment, Technology and Society) learning model. The research subjects were grade 2 students at SDN 221 Babakan Sentral. This study uses a classroom action research method which is divided into two stages. Each stage includes four steps: plan, implement, observe, and evaluate. Information is collected by observing and testing learning outcomes. The research results show that the application of the SETS model can improve student PLH learning outcomes. This increase can be seen from the increase in the average class score and the percentage of student learning completion from cycle I to the next cycle. Apart from that, the SETS model also increases students' active participation in learning and their ability to relate PLH concepts to science, technology and society. In conclusion, the SETS learning model is effective in improving learning outcomes and students' understanding of PLH material.